Regional conference on the problems of land tenure and decentralization - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
regional conference on land tenure problems related to government and decentralization policies will take place in Praia, Cape Verde, from 21-25 March, 1994